PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA DOSEN UNIVERSITAS PAMULANG - Sutoro, Moh (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
Tri Dharma is a classic problem. Again, limitations and barriers are used as reasons. To answer this, a study of factors influencing lecturer performance was conducted. The quantitative approach was chosen because it has advantages, therefore the method of analysis uses multiple linear regression. The number of samples is 100 people and the sampling technique used is simple random sampling. The research instrument used the method of distributing questionnaires with a closed statement form. The results showed that compensation had a significant effect on performance with a regression coefficient of 0,502. Motivation has a significant effect on performance with a regression coefficient of 0,328. Simultaneously, compensation and motivation significantly influence performance with a determination coefficient of 44,9%. This confirms the theory, that the implementation of Tri Dharma required HR factors